La gloria de la pobreza: emergencia de actores frente a programas de asistencia social; The glory of poverty: emergence of actors at the forefront of social welfare programs - Zárate Hernández, José Eduardo; Cortés Marquez, Nubia (Universidad Autónoma Metropolitana, 2019)
The objective of this text is to analyze how stemming from the promotion of welfare programs in localities denominated as poor, new political actors with direct impact in the form of the local organization have emerged. The “eligible subject” of support has created unheard of forms of social exclusion, at the time in which it has generated various means to administer their life. The presented argument is based on fieldwork, semi-structured interviews, personal archive data collection and bibliographic research. The benefits granted by welfare programs have multiple conceptions among eligible subjects, which transcend the economical.; El objetivo del texto es analizar cómo, a partir de la promoción de programas sociales en localidades llamadas pobres, han emergido nuevos actores políticos con impactos directos en la forma de organización local. El “sujeto elegible” de apoyo ha creado formas de exclusión social inéditas, al tiempo que ha generado formas varias de administrar su vida. El argumento presentado se sustenta en trabajo de campo, entrevistas semiestructuradas, recopilación de datos de archivos personales de investigación bibliográfica. El beneficio otorgado por programas sociales tiene múltiples nociones entre los sujetos elegibles, las cuales trascienden lo económico.